2010
DOI: 10.1093/ndt/gfq375
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in non-critically ill children treated with aminoglycoside antibiotics in a tertiary healthcare centre: a retrospective cohort study

Abstract: AKI is common and associated with poorer outcomes in non-critically ill children treated with AG. Future research should attempt to understand how to best define AKI in the non-critical illness paediatric setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 41 publications
4
101
3
1
Order By: Relevance
“…Depending on the definition used, AKI occurred in 37%-51% of at-risk hospitalizations; at-risk was defined as having a baseline and at least one additional creatinine obtained. This is consistent with previously published reports using newer, standard definitions based on creatinine change (8,13,18,19). Our study also suggests that much pediatric AKI is of mild severity as 45%-53% of cases were classified as stage 1.…”
Section: Discussionsupporting
confidence: 93%
“…Depending on the definition used, AKI occurred in 37%-51% of at-risk hospitalizations; at-risk was defined as having a baseline and at least one additional creatinine obtained. This is consistent with previously published reports using newer, standard definitions based on creatinine change (8,13,18,19). Our study also suggests that much pediatric AKI is of mild severity as 45%-53% of cases were classified as stage 1.…”
Section: Discussionsupporting
confidence: 93%
“…[10][11][12] Recent studies have found AKI among noncritically ill patients to be associated with exposure to multiple nephrotoxins and to aminoglycoside antibiotics specifi cally. 11,12 Accurate detection of AKI relies on serial measurements of serum creatinine (SCr) level or urine output over time. 13 However, noncritically ill pediatric patients are often not monitored for AKI and providers may miss an opportunity to prevent or diagnose AKI.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…13 However, noncritically ill pediatric patients are often not monitored for AKI and providers may miss an opportunity to prevent or diagnose AKI. 11,12 The epidemiology of nephrotoxin-associated AKI on a large scale is therefore not well understood.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
See 2 more Smart Citations